Red Fluorescent Turn‐On Ligands for Imaging and Quantifying G Protein‐Coupled Receptors in Living Cells. Issue 3 (21st January 2014) - Karpenko, Iuliia A.; Kreder, Rémy; Valencia, Christel; Villa, Pascal; Mendre, Christiane; Mouillac, Bernard; Mély, Yves; Hibert, Marcel; Bonnet, Dominique; Klymchenko, Andrey S.
Abstract Classical fluorescence‐based approaches to monitor ligand–protein interactions are generally hampered by the background signal of unbound ligand, which must be removed by tedious washing steps. To overcome this major limitation, we report here the first red fluorescent turn‐on probes for a G protein‐coupled receptor (oxytocin receptor) at the surface of living cells. The peptide ligand carbetocin was conjugated to one of the best solvatochromic (fluorogenic) dyes, Nile Red, which turns on emission when reaching the hydrophobic environment of the receptor. We showed that the incorporation of hydrophilic octa(ethylene glycol) linker between the pharmacophore and the dye minimized nonspecific interaction of the probe with serum proteins and lipid membranes, thus ensuring receptor‐specific turn‐on response. The new ligand was successfully applied for background‐free imaging and quantification of oxytocin receptors in living cells.